A survey of British rheumatologists' DMARD preferences for rheumatoid arthritis. - Jobanputra, P; Wilson, J; Douglas, K; Burls, A (2004)
OBJECTIVE: To determine the current disease-modifying anti-rheumatic drug (DMARD) preferences of UK consultant rheumatologists. METHODS: A questionnaire was sent in May 2002. We asked which DMARD(s) was most frequently preferred first and sought the most typical sequence of DMARDs, including DMARD combinations. Also we determined the extent to which prognostic and other factors influenced treatment choices. Comments were invited, written responses abstracted and key themes identified. RESULTS: After two mailings, 331 (of 460; 72%) suitable questionnaires were returned. Ninety-five per cent (315/331) preferred methotrexate (154, 46.5%) or sulphasalazine (144, 43.5%) or either of these two (17, 5%) as first-choice agent. Of those who chose methotrexate first, 80% (123/154) ranked sulphasalazine second, 45% (55/123) combined sulphasalazine and methotrexate and 49% (27/55) then added hydroxychloroquine to this combination, in active disease. Of those who chose sulphasalazine first, 95% (137/144) ranked methotrexate second, 75% (113/150) preferring methotrexate monotherapy and 12% (18/150) the combination with sulphasalazine. Rheumatologists who preferred sulphasalazine first more commonly used subsequent DMARDs singly than those who started with methotrexate (P < 0.0001). Leflunomide was more commonly preferred than intramuscular gold as third choice (52/145 vs 29/145; P < 0.003). The most popular sequence of DMARDs was methotrexate or sulphasalazine, singly or in combination, leflunomide, intramuscular gold and anti-tumour necrosis factor therapy. Poor prognostic factors influenced DMARD choice, but patient occupation and drug costs did not. CONCLUSION: Methotrexate has displaced other DMARDs, especially sulphasalazine, as agent of first choice and newer agents have displaced older DMARDs. Whether the expressed preference for particular DMARDs accurately reflects actual use, and is optimal in rheumatoid arthritis, remains to be determined.